Autoridade docente em tempos de pós-verdade - Ceretta, Patrício (2023)
doing. It seeks to understand teaching authority and how it stands in this time of Fake News, of pre-made truths, in which people want to believe in something without any concern about its legitimacy. To this end, we sought to answer the following research problem: to what extent does post-truth interfere in teaching authority and if it has an influence particularly on teachers' doing and on education as well. Methodologically, the study has a bibliographic character and is based on a qualitative approach of Hans-Georg Gadamer's philosophical hermeneutics perspective (2015) and Hannah Arendt's reflections (1992). Other contemporary authors reference the discussions on post-truth and fake news, among them are: Dunker (2017), D'ancona (2019), Keyes (2018), and Santella (2019). Specifically, it seeks to investigate which concept of (teaching) authority it is possible to glimpse from Hannah Arendt’ thought and HansGeorg Gadamer, notably from the notions of responsibility and recognition. Furtermore, to highlight the relationship and consequences between teaching authority and post-truth, trying to identify how the understanding of authority proposed by Arendt and Gadamer can contribute to the teaching education process beyond the current conception. The thesis is that the social degradation of truth, indirectly proposed by post-truth, directly affects some areas of society, such as politics, and, in particular whay education, because when truth get lost, it threatens the future of those who come into the world. In this way, it is evident that the crisis of teaching authority is directly related to the political crisis afflicting society, since authoritarian and conservative governments tend to discredit teaching process, because they know that teaching authority strengthens the students' critical sense, making them aware of the present time's demands, creating self-awareness of the past and a vision of the future that can provide an opportunity for a step forward in the construction of history. In this way, broadening the perception that relationships go beyond feelings and individual perceptions, concerns a belonging to a real group of people who need to strengthen each other to face a time that relativizes the most elementary education's issues. This is because what is at stake is the human being himself, his relationships, and his decisions when facing the new challenges of the present time.